Understanding open source and free software licensing - St. Laurent, Andrew M. (O'Reilly, 2004)
If you've held back from developing open source or free software projects because you don't understand the implications of the various licenses, you're not alone. Many developers believe in releasing their software freely, but have hesitated to do so because they're concerned about losing control over their software. Licensing issues are complicated, and both the facts and fallacies you hear word-of-mouth can add to the confusion. Understanding Open Source and Free Software Licensing helps you make sense of the different options available to you. This concise guide focuse.